Combined Dual Channel Impedance/pH-metry in Patients With Suspected Laryngopharyngeal Reflux - Lee, Bong Eun (Korean Society of Neurogastroenterology and Motility, 2010)
BACKGROUND/AIMS: Laryngopharyngeal symptoms of gastroesophageal reflux disease (GERD) such as globus sensation, hoarseness and chronic cough are becoming increasingly recognized. This study was aimed to investigate the diagnostic usefulness of combined dual channel multichannel intraluminal impedance (MII)/pH-metry in 'off-proton pump inhibitor (PPI)' patients with suspected laryngopharyngeal reflux. METHODS: Ninety-eight patients with laryngopharyngeal symptoms of GERD were included. All patients were 'off-PPI' state for at least 2 weeks prior to the study, and underwent endoscopy and dual channel combined MII/pH-metry. RESULTS: The mean age of the patients was 49.8 ± 10.9 years and there were 44 males (44.9%). Fifty-three patients (54.1%) showed pathologic gastroesophageal reflux (GER). Combined dual channel MII/pH-metry achieved highest diagnostic yield of 49.0% and diagnostic yield of single channel combined MII/pH-metry was 37.8%. Addition of MII to standard pH-metry increased twofold of the diagnostic yield for detecting GER. Among 37 patients (37.8%) who had pathologic GER being detected by MII/pH-metry, 19 patients (19.4%) had nonacid GER (nonacid GER group) while 18 patients (18.4%) had acid GER (acid GER group). Pathologic GER group, as classified by MII/pH-metry showed more frequent globus sensation than nonpathologic GER group. Acid GER group had more proximal reflux than nonacid GER group, especially in the upright position. CONCLUSIONS: In this study, combined dual channel MII/pH-metry showed the highest diagnostic yield for detecting GER. This technique can be performed primarily to accurately diagnose laryngopharyngeal reflux disease and exclude other causes of laryngopharyngeal symptoms.